1998
DOI: 10.1111/j.1574-6968.1998.tb13075.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron microscopic localisation of the OMP90 family on the outer membrane surface ofChlamydia psittaci

Abstract: The putative outer membrane location of the OMP90 (formerly POMP) family from the ovine abortion strain of Chlamydia psittaci was investigated by immunoelectron microscopy. Using a non-embedding technique, antigens were shown to be localised on the outer membrane surface of both elementary and reticulate bodies, the infectious and non-infectious forms of Chlamydiae respectively. Antibodies affinity-purified against the expressed amino- and carboxy-terminal halves of one of the family members. OMP90A, demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Pmps are characterized by having repeated GGAI motifs. In addition, a C-terminal phenylalanine and cleavable signal peptides, suggest that some Pmps are localized in the outer membrane [53], which was confirmed in several recent studies [54][55][56]. Although, the function of Pmps in unknown, it is possible that they are implicated in evading the immune response through antigenic variation [57].…”
Section: Important General Findingssupporting
confidence: 51%
“…Pmps are characterized by having repeated GGAI motifs. In addition, a C-terminal phenylalanine and cleavable signal peptides, suggest that some Pmps are localized in the outer membrane [53], which was confirmed in several recent studies [54][55][56]. Although, the function of Pmps in unknown, it is possible that they are implicated in evading the immune response through antigenic variation [57].…”
Section: Important General Findingssupporting
confidence: 51%
“…Nine of these consensus tripeptides (ten for POMP 91B) were located in the Nterminus of the amino acid sequences within a 200 amino acid domain (amino acids 27-223 in POMP 91B). It is worth noting that immunoelectronic microscopy has demonstrated that this domain is accessible to antibodies utilized in this study on the chlamydial outermembrane surface (Longbottom et al, 1998b). The majority of the remaining sites reside in the second half of the C-terminal part of the molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments using electron microscopy have shown that the epitope of mAb 181 is accessible to the antibody on the surface of EBs. These data have led to the suggestion that at least one of the three POMPs at 90 kDa reacting with this mAb is surface exposed (Longbottom et al, 1998b). We examined the orientation of the oligosaccharides attached to the POMPs by treating EBs with glycosidase under non-denaturing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOMP sequence variation has only been found in C. trachomatis to date, and C. psittaci and C. pneumoniae strains that have invariant MOMP sequence (Gaydos et al, 1992 ;Zhao et al, 1993) can indeed infect susceptible hosts at different anatomical sites, and indeed different hosts (Girjes et al, 1994). More interestingly, genomic sequencing has uncovered gene families encoding high molecular mass (90-180 kDa) polymorphic membrane proteins (Pmps) (also named POMPs or OMPs), some of which have been demonstrated to be exposed at the surface (Knudsen et al, 1999 ;Longbottom et al, 1998a). Families of 9 and 21 pmp genes have been identified in C. trachomatis and C. pneumoniae, respectively (Kalman et al, 1999 ;Read et al, 2000 ;Stephens et al, 1998), and five gene family members have been identified to date in ovine C. psittaci (Longbottom et al, 1998b) …”
Section: Chlamydia Antigenic Variationmentioning
confidence: 99%